2022
DOI: 10.3390/microorganisms10081635
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Biological Control of Pythium schmitthenneri Root Rot Disease of Olive Trees (Olea europaea L.) by Antagonistic Bacteria

Abstract: Several diseases affect the productivity of olive trees, including root rot disease caused by Pythium genera. Chemical fungicides, which are often used to manage this disease, have harmful side effects on humans as well as environmental components. Biological management is a promising control approach that has shown its great potential as an efficient eco-friendly alternative to treating root rot diseases. In the present study, the antagonistic activity of ten bacterial isolates was tested both in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…and the bacterial isolates Serratia odorifera and Pseudomonas fluorescens, the results revealed the ability of these bacterial species to inhibit the mycelial growth of the mentioned fungal pathogens [57]. The Bacillus genus has been extensively employed as a microbial biopesticide to its high inhibitory effect on mycelial growth in many studies [31,[58][59][60][61]. A study conducted by Liu et al [62] demonstrated that using Bacillus amyloliquefaciens, B. velezensis, B. siamensis, B. subtilis, and B. atrophaeus as a composite microbial culture resulted in a significant reduction in the abundance of Fusarium sp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…and the bacterial isolates Serratia odorifera and Pseudomonas fluorescens, the results revealed the ability of these bacterial species to inhibit the mycelial growth of the mentioned fungal pathogens [57]. The Bacillus genus has been extensively employed as a microbial biopesticide to its high inhibitory effect on mycelial growth in many studies [31,[58][59][60][61]. A study conducted by Liu et al [62] demonstrated that using Bacillus amyloliquefaciens, B. velezensis, B. siamensis, B. subtilis, and B. atrophaeus as a composite microbial culture resulted in a significant reduction in the abundance of Fusarium sp.…”
Section: Discussionmentioning
confidence: 98%
“…Bacteria, particularly those belonging to the genera Bacillus, Pseudomonas, and Enterobacter, have demonstrated their potential as biological control agents against various plant pathogens, including P. vexans [26][27][28][29]. These bacteria can inhibit the growth and development of phytopathogens by producing antibiotics, lytic enzymes, and siderophores that deprive the pathogen of essential resources or directly lyse its cells [30][31][32]. In addition to their antagonistic activity, some bacteria-namely, PGPR-possess plant growth-promoting properties that can improve plant vigor and productivity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Measures such as crop rotation, soil solarization, and mostly the use of fungicides, have been implemented to control these pathogens. Recently, effectiveness of Alcaligenes faecalis ACBC1 and Bacillus amyloliquefaciens SF14 to manage olive root rot caused by P. schmitthenneri was reported (Legrifi et al, 2022a).…”
Section: Oomycetesmentioning
confidence: 99%
“…Additionally, the bacterial cell-free filtrates also demonstrated a significant inhibition of the pathogen mycelial growth. To validate their findings obtained in vitro, Legrifi et al [4] conducted greenhouse tests. Among the bacterial isolates, Alcaligenes faecalis ACBC1 and Bacillus amyloliquefaciens SF14 emerged as the most successful in controlling the severity of olive root rot disease.…”
mentioning
confidence: 99%
“…In their study, Legrifi et al [4] focused on evaluating the potential of ten bacterial strains, isolated from the rhizosphere of citrus and blossoms of pear, apple, and quince trees, for their ability to suppress the mycelial growth of Pythium schmitthenneri, a pathogenic agent causing root rot disease in olive trees. These bacterial strains belonging to the genera Alcaligenes, Bacillus, Pantoea, Sphingobacterium, and Stenotrophomonas, were selected for their antagonistic properties against various pathogens [5].…”
mentioning
confidence: 99%